Beyond Recidivism : New Approaches to Research on Prisoner Reentry and Reintegration - Maruna, Shadd; Leverentz, Andrea; Leverentz, Andrea; Christian, Johnna; Christian, Johnna; Chen, Elsa Y.; Chen, Elsa Y. (Book collections on Project MUSE., 2020)
Understanding reentry experiences after incarcerationPrison in the United States often has a revolving door, with droves of formerly incarcerated people ultimately finding themselves behind bars again. In Beyond Recidivism, Andrea Leverentz, Elsa Y. Chen, and Johnna Christian bring together a leading group of interdisciplinary scholars to examine this phenomenon using several approaches to research on recently released prisoners returning to their lives. They focus on the social context of reentry and look at the stories returning prisoners tell, including such key issues as when they choose to reveal (or not) their criminal histories. Drawing on contemporary studies, contributors examine the best ideas that have emerged over the last decade to understanding the challenges prisoners face upon reentering society. Together, they present a complete picture of prisoner reentry, including real-world recommendations for policies to ensure the well-being of returning prisoners, regardless of their past mistakes.